Programming virulent bacteriophages by developing a multiplex genome engineering method - Hailin Zhang; Ru Zhu; Zhaofei Wang; Ruoting He; Yuran Zhang; Ji Luan; Yaxian Yan; Youming Zhang; Hailong Wang (mBio)
ABSTRACT The use of virulent bacteriophages (phages) against pathogenic bacteria has recently attracted considerable interest. The limitations of naturally isolated phages have promoted the development of genome engineering methods to optimize their functions; however, engineering of virulent phage genomes in bacterial hosts remains challenging. Here, we describe a SMART (splitting, modifying, assembling, and rebooting) method for multiplex genome engineering of virulent phages by splitting the genome into multiple segments cloned and inserted into single-copy bacterial artificial chromosome vectors in Escherichia coli to overcome the toxicity of phage gene products, modifying multiple targeted loci in parallel through recombineering, assembling split segments into an intact genome, and rebooting the recombined phage in bacterial hosts. Using the SMART method, the 39.9-kb T7 E. coli phage genome was split into 10 segments, and 8 genomic loci were deleted in parallel to obtain a chassis phage with 10% genome reduction. The insertion capacity of the chassis phage genome and the expression levels of exogenous genes at different loci were evaluated. Finally, a synthetic T7 phage that efficiently lyses widely different bacteria, such as E. coli, Staphylococcus aureus, and Streptococcus agalactiae, was constructed by expressing heterologous lysins from Staphylococcus and Streptococcus phages. SMART will facilitate the programming and understanding of the genome structure and function of virulent phages.IMPORTANCEUnlike temperate phages, which integrate into host genomes and allow time for genetic manipulation, lytic phages rapidly hijack the bacterial machinery and trigger host lysis within minutes, leaving an extremely narrow editing window. Furthermore, virulent phage genes usually encode toxic products that inhibit the growth of bacterial hosts. We developed a SMART (splitting, modifying, assembling, and rebooting) method for multiplex genome engineering of virulent phages. We deleted 3.9 kb sequences distributed across 8 sites in the 39.9 kb genome of the wild-type T7 Escherichia coli phage to construct a chassis phage. Synthetic T7 phages expressing heterologous lysin genes were constructed to efficiently lyse different bacteria, such as E. coli, Staphylococcus aureus, or Streptococcus agalactiae. The SMART method will facilitate targeted modifications of phage genomes for the creation of custom-designed phages with enhanced therapeutic efficacy, broader host specificity, and programmable behaviors.